DEVELOPMENT OF STRATEGIC COMPETENCE OF STUDENTS IN ENGLISH - Atabekova Feruza Khujamqulovna (Journals Park Publishing, 2022)
The article reflects the methods and innovative approaches to the development of strategic competence of students in English. It was used in the scientific developments of foreign and domestic scientists in covering the topic of the article. The results obtained from the article can be used in the training of students in the direction of a nofilologist.
Keywords: language, lexical, feature, reality, temperament, methodology, competence.